2013
DOI: 10.1016/j.actatropica.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Antidermatophytic and antileishmanial activities of essential oils from Lippia gracilis Schauer genotypes

Abstract: Lippia gracilis, popularly known in Brazil as 'alecrim-de-tabuleiro', is used for many purposes, especially antimicrobial and antiseptic activities. The leaves of three L. gracilis genotypes, including LGRA-106, LGRA-109 and LGRA-110 were collected from the Active Germplasm Bank located in the "Campus Rural da UFS" research farm at the São Cristóvão country, Sergipe State, Brazil. The essential oils were obtained from leaves of L. gracilis plants by hydrodistillation. Chemical analysis of the essential oils wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 30 publications
4
24
1
5
Order By: Relevance
“…Dentre os vários produtos extraídos a partir desses vegetais, os mais citados em artigos científicos são os constituintes voláteis ou óleos essenciais e extratos alcoólicos, sendo os mais comuns etanol, metanol e acetato de etila das partes aéreas das amostras botânicas, principalmente as folhas (secas ou frescas), muito embora a raiz também seja citada esporadicamente (Oliveira et al 2014, Santos et (Bandeira et al 2014, Geromini et al 2012, Mamun-Or-Rashid et al 2012, Bitu et al 2012, Gracia-Valenzuela et al 2012, Correa-Royero et al 2010, Fontenelle et al 2007, Sena Filho et al 2006) e são usualmente associadas à composição química de seus óleos e extratos, reportados em alguns trabalhos como ricas fontes de constituintes de natureza fenólica (López et al 2011, Lemos et al 1990, sendo apontadas como importantes recursos etnofarmacológicos para tratar doenças dermatológicas, respiratórias e gastrointestinais, bem como potencial sedativo, analgésico, antipirético, antihipertensivo e antiespasmódico (Batista et al 2013, Melo et al 2013, Geromini et al 2012, Hennebelle et al 2008a, Castro 2002, Salimena 2002, Pascual et al 2001a.…”
Section: Resultsunclassified
“…Dentre os vários produtos extraídos a partir desses vegetais, os mais citados em artigos científicos são os constituintes voláteis ou óleos essenciais e extratos alcoólicos, sendo os mais comuns etanol, metanol e acetato de etila das partes aéreas das amostras botânicas, principalmente as folhas (secas ou frescas), muito embora a raiz também seja citada esporadicamente (Oliveira et al 2014, Santos et (Bandeira et al 2014, Geromini et al 2012, Mamun-Or-Rashid et al 2012, Bitu et al 2012, Gracia-Valenzuela et al 2012, Correa-Royero et al 2010, Fontenelle et al 2007, Sena Filho et al 2006) e são usualmente associadas à composição química de seus óleos e extratos, reportados em alguns trabalhos como ricas fontes de constituintes de natureza fenólica (López et al 2011, Lemos et al 1990, sendo apontadas como importantes recursos etnofarmacológicos para tratar doenças dermatológicas, respiratórias e gastrointestinais, bem como potencial sedativo, analgésico, antipirético, antihipertensivo e antiespasmódico (Batista et al 2013, Melo et al 2013, Geromini et al 2012, Hennebelle et al 2008a, Castro 2002, Salimena 2002, Pascual et al 2001a.…”
Section: Resultsunclassified
“…At present, individual activities of these compounds have been proven [20]. Moreover, different studies have shown potent antileishmanial activities of these compounds such as terpenic derivatives, carvacrol, p -cymene, thymol, carvone, limonene, and terpinene [2730]. Therefore, the presence of these phytoconstituents in P. khinjuk extract could be responsible for their antileishmanial effect though their exact mode of action is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Monoterpenes with this type of activity is still to be investigated, despite of a number of medicinal plants have been introduced having anti-leishmaniasis potential [36][37][38][39][40][41][42][43][44]. Saponins from Calliandra pulcherrima and Quillaja saponaria were found to exhibit significant anti-leishmaniasis activity against Leishmania donovani and L. chagasi.…”
Section: Anti-leishmaniasis and Anti-chagas Disease Potentialsmentioning
confidence: 99%